2020
DOI: 10.1016/j.jecp.2020.104890
|View full text |Cite
|
Sign up to set email alerts
|

2.5-year-olds succeed in identity and location elicited-response false-belief tasks with adequate response practice

Abstract: Researchers have argued that traditional elicited-response false-belief tasks involve considerable processing demands and hence underestimate children's false-belief understanding. Consistent with this claim, Setoh et al. (2016) recently found that when processing demands were sufficiently reduced, children could succeed in an elicited-response task as early as 2.5 years of age. Here we examined whether 2.5-year-olds could also succeed in a low-demand elicitedresponse task involving false beliefs about identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…Our results suggest that children with ASD can understand others' false beliefs when cognitive demands are sufficiently reduced, but their false-belief processing unfolds more slowly than in TD children. Our findings are thus broadly consistent with recent evidence demonstrating that task demands impact false-belief performance (Rubio-Fernández and Geurts, 2013;Chevallier et al, 2014;Setoh et al, 2016;Carlsson et al, 2018;Bialecka-Pikul et al, 2019;Psouni et al, 2019;Salter and Breheny, 2019;Scott et al, 2020). More generally, this study offers a promising new paradigm exploring social cognitive processing in children with ASD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results suggest that children with ASD can understand others' false beliefs when cognitive demands are sufficiently reduced, but their false-belief processing unfolds more slowly than in TD children. Our findings are thus broadly consistent with recent evidence demonstrating that task demands impact false-belief performance (Rubio-Fernández and Geurts, 2013;Chevallier et al, 2014;Setoh et al, 2016;Carlsson et al, 2018;Bialecka-Pikul et al, 2019;Psouni et al, 2019;Salter and Breheny, 2019;Scott et al, 2020). More generally, this study offers a promising new paradigm exploring social cognitive processing in children with ASD.…”
Section: Discussionsupporting
confidence: 92%
“…First, reducing the demands of elicited-response tasks enables TD children to pass at younger ages (e.g., Chandler et al, 1989;Lewis and Osborne, 1990;Bartsch, 1996;Rubio-Fernández and Geurts, 2013;Bialecka-Pikul et al, 2019;Psouni et al, 2019;Salter and Breheny, 2019). In particular, several recent studies have found that even 2.5-years-olds can pass elicited-response tasks when both the response-generation and response-inhibition demands are sufficiently reduced (Setoh et al, 2016;Grosso et al, 2019;Scott et al, 2020).…”
mentioning
confidence: 99%
“…This proved enough to raise two-and-a-half-year-olds above-chance, an unprecedented result at the time. Importantly, this finding has since been replicated (Grosso et al, 2019;Kaltefleiter et al, 2021) and extended (Scott et al, 2020).…”
Section: Processing-load Accountsmentioning
confidence: 68%
“…What about response-generation practice trials? These are likely to have helped by facilitating, through either priming or automatization, response-generation processes, including both processing the test question and selecting a response (Scott et al, 2020). Notably, although priming and automatization may result in lower processing-demands, they are also known to result in faster processing.…”
Section: Evidence For Processing-load Accountsmentioning
confidence: 99%